Trends for Clinical Trials on Medicinal Products for Neurological Disorders in Lithuania and Europe - Emilijus Žilinskas; Arūnas Vaitkevičius (Neurologijos seminarai, 2024)
Background. As the global burden of neurological diseases has been increasing, clinical trials have become more important. Yet, no systematic analysis of clinical trials of neurological medicinal products has been done in Europe and, specifically, in Lithuania. The aim of this study is to evaluate the tendencies of characteristics and registration dynamics of clinical trials of neurological medicines in Europe and Lithuania.Materials and methods. Analysis of data from the clinical trials register of the European Union drug regulatory authorities (EudraCT) has been performed. Applications of clinical trials of neurological medicines included in the register during the period between 2012–2021 have been reviewed. The following aspects have been evaluated: the phase of the trial, the sponsor status, the neurological condition (indication), the expected sample size of the trial, the trial design, and the number of member countries.Results. 2,242 clinical trials of neurological medicines have been registered in Europe during the period of 2012–2021, and they comprised 6.49% of all clinical trials registered in Europe. The annual registration rates did not change significantly during the period of 2012–2021 (R² = 0.039; p = 0.606). The majority of the trials (72.18%) were sponsored by commercial pharmaceutical companies. Most trials (31.73%) were registered as phase I trials. The majority of the trials (363 (17.20%)) were clinical trials for Alzheimer’s disease and other dementias. During the period of 2012–2021, there was a significant decrease in the annual registration rate of clinical trials for Alzheimer’s disease and other dementias (R² = 0.751, p = 0.001) and an increase of clinical trials for myoneural junction and muscle diseases and motor neuron disease (R² = 0.582, p = 0.010 and R² = 0.635, p = 0.006, accordingly). Commercial trials had a higher planned number of subjects (p = 0.014). Multiple member states participated in commercial trials more frequently (p < 0.001). Fifty-five clinical trials of neurological medicines were registered in Lithuania during the period of 2012–2021, and they comprised 8.08% of all clinical trials registered in Lithuania. The annual registration rate has decreased significantly (R² = 0.401, p = 0.049). Almost all trials in Lithuania (53 out of 55) were sponsored by commercial companies. The majority of trials (23 (42%)) were trials for demyelinating diseases of the CNS.Conclusions. The annual registration rates of trials of neurological medicines remain stable in Europe while decreasing in Lithuania. Commercial clinical trials have more participants, and are more commonly conducted in multiple member states.